La conducta y las relaciones interpersonales que presentan los escolares del cuarto año de educación básica paralelo “B” de la unidad educativa Pío Jaramillo Alvarado. Periodo lectivo 2018 - Calderón Castillo, Gianella Michelle (2018)
For this thesis on: the behavior and interpersonal relationships presented by the students of the fourth year of basic education "B" parallel of the Pio Jaramillo Alvarado Educational Unit. Class Period 2018; With the purpose of contributing to school children who present behavioral problems by generating an adequate interpersonal relationship between the child and his / her classmates in order to avoid behavior problems; This being a qualitative research; Through methods employed such the scientist, analytic-synthetic and inductive; In the same way, the instruments used were the ICAP Inventory of Behavior Inventory for Service Planning and Individual Programming (section E, Behavior Problems), Life at School and an interview addressed to teachers who work with schoolchildren in a sample of 26 students, to identify difficulties such as: disruptive, non-collaborative, self-injurious, hetero-aggressive, destructive, social-offensive behaviors and how they affect their interpersonal relationships. It is concluded that the behavioral problems that students present most often are disruptive and non-collaborative, generating difficulties in their interpersonal relationships, which is why a plan of activities aimed at modifying behavior and improving interpersonal relationships is applied. The result was a clear improvement in the majority of students, validating each of the activities.